A REVIEW OF COGNITIVE LINGUISTIC APPROACHES TO TEACHING VOCABULARY TO EFL LEARNERS - Tran Tin Nghi (2023)
The amount of learners’ vocabulary is the most important factor in detecting students’ proficiency, competence, and level of learners of English. Vocabulary teaching methods have been appealed to linguists, especially in the TESOL field. This paper aims to discuss three cognitive-linguistic principles in teaching vocabulary for EFL learners of English, namely the study of categorization, prototype, and metaphor. The findings of this research provide light on how EFL learners deal with particular figurative interpretations of lexical items whose core meanings they are familiar with and may therefore help to the improvement of existing methods to vocabulary instruction in the early English process. Categorization, Prototype, and Metaphor are used as guidelines to explore how target language words or phrases acquired figurative meanings (i.e., to identify their polysemous nature) and to facilitate not just their understanding, but also their learning of related phraseology. The implications of these principles in the EFL learning environment, like the Vietnamese context, are applicable and practical.